Thermodynamic and surface properties of Sr–Si Liquid Alloy at Different Temperatures - Mehta, Upendra; Gohivar, Ramesh K; Yadav, Shashit Kumar (The Journal of Knowledge and Innovation, 2023)
Thermodynamic and surface properties of Sr–Si liquid alloy have been estimated and explained at different temperatures using quasi–lattice model and Butler’s model respectively. The interaction energy parameters, also called model parameters have been determined using the available literature data for excess Gibbs free energy of mixing. The reliability of the model parameters has been obtained by comparing the results of present work with the values of thermodynamic functions calculated using literature data. The mixing behaviour of the system have been analysed by reproducing the thermodynamic, structural and surface properties of the system at 1080 K using optimised model parameters. The temperature dependence of model parameters have been then calculated by assuming their temperature derivative terms to be constant for small change in temperature of the system.